2018
DOI: 10.22531/muglajsci.383095
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability and Tailings Management in the Mining Industry: Paste Technology

Abstract: In this study, the basic principles of paste technology which has been implemented successfully in the mining industry for both waste volume reduction and environmental impact reduction were investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 26 publications
(23 reference statements)
0
6
0
Order By: Relevance
“…Binders account for approximately 75% of the total cost of CPB [22,23]. Increasing the binder content can enhance the mechanical properties of CPB, but it will result in higher costs [24][25][26]. Further, cement clinker production is associated with high carbon dioxide emissions [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Binders account for approximately 75% of the total cost of CPB [22,23]. Increasing the binder content can enhance the mechanical properties of CPB, but it will result in higher costs [24][25][26]. Further, cement clinker production is associated with high carbon dioxide emissions [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…As an environmentally friendly mining method, the filling mining method can improve resource recovery rate, control rock migration and surface subsidence, treat solid waste accumulation, improve stope environment and prolong mine service life so as to reduce the influence and damage of resource mining on natural, social and living environment [ 1 , 2 , 3 , 4 , 5 , 6 ]. The technology has been successfully applied in various engineering environments in many countries [ 7 , 8 , 9 ]. The Yushenfu mining area in northern Shaanxi is located at western China’s edge of the Maowusu Desert.…”
Section: Introductionmentioning
confidence: 99%
“…Many types of researches indicated that the loading rate has a significant effect on the properties of materials. Different materials such as rock, concrete, and backfill exhibit different behaviors under different loading rates [15][16][17].…”
Section: Introductionmentioning
confidence: 99%